2023
DOI: 10.1039/d3ra04402e
|View full text |Cite
|
Sign up to set email alerts
|

Facile one-step hydrothermal synthesis of monolayer and turbostratic bilayer n-doped graphene quantum dots using sucrose as a carbon source

Akkawat Ruammaitree,
Kanyaporn Praphanwong,
Arunocha Taiphol

Abstract: In this study, the thickness distribution and interlayer spacing of n-doped graphene quantum dots are revealed by X-ray diffraction curve fitting, which is calculated using a simple and accurate equation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
1
0
Order By: Relevance
“…249 Furthermore, the number of layers in GQDs can be confirmed through atomic force microscopy (AFM) and X-ray diffraction (XRD) analysis. 247,250 Recently, Ruammaitree et al conducted the bottom-up hydrosolvothermal synthesis using sucrose and ethylenediamine as precursors, followed by purifi-cation using a MW500 dialysis bag to obtain N-doped GQDs. 250 The size distribution of the obtained GQDs ranged from 3 to 20 nm (with an average size of 16.7 nm) and these GQDs exhibited relatively larger sizes compared with other reports that utilized MW500 dialysis bags.…”
Section: Controlling Self-assembly Of Gqdsmentioning
confidence: 99%
“…249 Furthermore, the number of layers in GQDs can be confirmed through atomic force microscopy (AFM) and X-ray diffraction (XRD) analysis. 247,250 Recently, Ruammaitree et al conducted the bottom-up hydrosolvothermal synthesis using sucrose and ethylenediamine as precursors, followed by purifi-cation using a MW500 dialysis bag to obtain N-doped GQDs. 250 The size distribution of the obtained GQDs ranged from 3 to 20 nm (with an average size of 16.7 nm) and these GQDs exhibited relatively larger sizes compared with other reports that utilized MW500 dialysis bags.…”
Section: Controlling Self-assembly Of Gqdsmentioning
confidence: 99%
“…Secondly, doping creates electron trap centers, boosting PL intensity and QY. Moreover, altering electron structures can enhance QY in specific wavelength ranges [158,163,164]. For instance, recent studies by Hung et al reported a 12.5% QY enhancement through sulfur (S) doping in pristine GQDs [158].…”
Section: Photoluminescence Properties Of Gqdsmentioning
confidence: 99%